Economic overview of Ireland and Northern Ireland - Bergin, Adele; McGuinness, Seamus; Banahan, Conor (ESRI, 2025)
This report provides a high-level comparison of the economies of Ireland and Northern Ireland (NI) for recent years. A range of economic, socio-economic and demographic measures are used to explore similarities and differences in economic growth, living standards, general well-being and economic structures. While the primary focus is to provide a comparison of the economies of Ireland and NI over recent years, we also examine changes over time to assess how relativities have evolved in recent years. It is important to recognise that the economies North and South on the island are distinct in important structural respects. NI forms a regional part of the overall United Kingdom (UK) economy with important implications, for instance, for NI’s trade and labour market flows, as well as the organisation of public services and public policy configuration. Comparisons with Ireland, as a national level economy, and a European Union (EU) Member State, will therefore not always be on a like-for-like basis. In making comparisons, it is also important to note the relatively strong economic growth in Ireland and the impact of Brexit on the whole of the UK in recent years, which additionally saw an absence of a functioning Northern Ireland Executive for a prolonged period. These wider contexts are reflected in metrics over recent years, but may not continue to impact in the same way in the time ahead.